Functional properties of palmyra palm (Borassus flabellifer L.) exocarp and mesocarp and its potential application - Mohd Hassan, Rodiah (2021)
Borassus flabellifer (B. flabellifer) with its immature and soft juicy seed nuts is popular as a natural refreshing drink. However, the peel (mesocarp and exocarp) is discarded and very negligible information is available on the potential of the peel as a food ingredient. The presence of bitterness (flabelliferins) in the peel could also be a deterrent to its acceptablility. This present study aimed to explore the physicochemical, composition and functional properties of the mesocarp and exocarp of B. flabellifer before and after removal of the bitter component with naringinase. The debittered mesocarp (DMP) was incorporated into a muffin to determine its effect on such product characteristics. The exocarp had significantly higher (p<0.05) insoluble dietary fibre than the mesocarp but lower soluble dietary fibre. Fructose, galactose, glucose, mannose, and sucrose were detected in both samples including phenol and tannins. Radical scavenging activity (157.05 mM TE/g) and reducing power (213.05 mM Fe2+) of the exocarp were significantly (p<0.05) higher compared to the mesocarp. Mesocarp and exocarp have good functional properties especially their water holding (7.11 and 5.99 g/g, respectively), swelling capacity (9.15 and 7.53%, respectively) and wettability (44.33 and 397.36 seconds, respectively). Subsequently, the mesocarp was selected for the enzymatic treatment, due to it has higher portion (39.6%- 50.3%) than exocarp (5.5%-6.0%) from the whole fruit peel. It was found that the debittering treatment of mesocarp was best carried out at naringinase concentration of 2.0 g/L, 5 h, pH 5.0 and at 55 °C. A 63.8% of flabelliferin was successfully removed from the mesocarp. The DMP had good water-holding (9.4 g/g), swelling capacities (7.8 g/g) and wettability (12.3 seconds). Scanning electron microscope image showed that the structure of DMP become smaller fragment and more porous after debittering treatment. The changes in sturucture had increase the DMP surface area and trap more water/oil molecules thus leads to a higher water/oil capacity. However, the solubility, swelling and wettability of DMP were markedly decreased. The substitution of DMP for wheat flour more than 1% resulted in a more compact muffin with a significant (p<0.05) increase in hardness and a significant (p<0.05) decrease in cohesiveness and resilience. The substitution of DMP in muffin formulations caused a significant (p<0.05) reduction in baking loss rate, specific volume and volume when the substitution level exceeded 3%. The DMP muffin had darker crumb and crust compared to control. The sensory quality of muffin with a 1% substitution of DMP was found closest to the control muffin with no significant different (p>0.05) of score for all quality attributes tested. Colour, appearance, aroma, taste/flavour and texture were perceived lower in a muffin with 3-6% substitution of DMP. DMP could be appropriate for use as food ingredients if bitterness was removed more than 60%. It is recommended that DMP be incorporated into low-calorie and high-fiber products such as baked confectioneries, noodles, meat products and breakfast cereals.